2017
DOI: 10.1007/s12571-017-0647-5
|View full text |Cite
|
Sign up to set email alerts
|

The importance and challenges of crop germplasm interdependence: the case of Bhutan

Abstract: An analysis of food crop germplasm flows into and out of Bhutan was carried out to determine the extent of reliance of Bhutanese agriculture on introduced germplasm. Methods used included literature review, key informant interviews, field visits and crop pedigree analysis. Bhutan has been introducing foreign germplasm since the 1960s. By December 2015, about 300 varieties of 46 food crops including several non-traditional crops were introduced. Germplasm sources include CGIAR centres such as IRRI, CIMMYT, ICAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Such flows are probably facilitated by Agricultural Development Projects (ADPs). Similar suggestion was made by MAHESH & RONNIE (2017). They reported that one of the routes through which germplasms could get in to a region is donor-assisted projects involved in agricultural development.…”
Section: Resultssupporting
confidence: 64%
“…Such flows are probably facilitated by Agricultural Development Projects (ADPs). Similar suggestion was made by MAHESH & RONNIE (2017). They reported that one of the routes through which germplasms could get in to a region is donor-assisted projects involved in agricultural development.…”
Section: Resultssupporting
confidence: 64%
“…Therefore, there is well in excess of 100 cultivars to fill the global annual market of 8500 to 10,500 Tg. As New Zealand provides 50 to 55% of this seed, there is increased motivation and economic benefits to breed elite cultivars for the market, and germplasm forms one the foundations for cultivar development, food, and agriculture (Ghimiray and Vernooy, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, agriculture is facing challenges for crop production and the plant research community needs to perform quantitative analyses of numerous plant traits in order to accelerate progress in breeding [3,4]. This is why crop germplasm collections are of tremendous importance since no production area is fully self-sufficient in genetic diversity to cover all producer and consumer demand [5]. A germplasm collection is ordinarily evaluated with morphological descriptors which is usually the first step for describing accessions and selecting genitors for breeding programs [6,7].…”
mentioning
confidence: 99%